The Use of a Disposable Umbilical Clamp to Secure an Umbilical Venous Catheter in Neonatal Emergencies—An Experimental Feasibility Study - Bernhard Schwaberger; Christoph Schlatzer; Daniel Freidorfer; Marlies Bruckner; Christina H. Wolfsberger; Lukas P. Mileder; Gerhard Pichler; Berndt Urlesberger (Children, 2021)
Recent guidelines recommend the umbilical venous catheter (UVC) as the optimal vascular access method during neonatal resuscitation. In emergencies the UVC securement may be challenging and time-consuming. This experimental study was designed to test the feasibility of new concepts for the UVC securement. Umbilical cord remnants were catheterized with peripheral catheters and secured with disposable umbilical clamps. Three different securement techniques were investigated. Secure 1: the disposable umbilical clamp was closed at the level of the inserted catheter. Secure 2: the clamp was closed at the junction of the catheter and plastic wings. Secure 3: the setting of Secure 2 was combined with an umbilical tape. The main outcomes were the feasibility of fluid administration and the maximum force to release the securement. This study shows that inserting peripheral catheters into the umbilical vein and securing them with disposable umbilical clamps is feasible. Rates of lumen obstruction and the effectiveness of the securement were superior with Secure 2 and 3 compared to Secure 1. This new approach may be a rewarding option for umbilical venous catheterization and securement particularly in low-resource settings and for staff with limited experience in neonatal emergencies. However, although promising, these results need to be confirmed in clinical trials before being introduced into clinical practice.